2005
DOI: 10.2337/diacare.28.11.2613
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Type 1 and Type 2 Diabetes in Adults Aged 30–49 Years

Abstract: OBJECTIVE -Incidence of type 1 diabetes is considered to be low in adults, but no study has been performed in Mediterranean countries.RESEARCH DESIGN AND METHODS -We extended the study base of the registry of the province of Turin, Italy, to subjects aged 30 -49 years in the period 1999 -2001 to estimate the incidences of type 1 and type 2 diabetes. Diagnosis of type 1 diabetes was based on permanent insulin treatment or a fasting C-peptide level Յ0.20 nmol/l or islet cell (ICA) or GAD (GADA) antibody positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(98 citation statements)
references
References 32 publications
7
85
3
Order By: Relevance
“…The diagnosis of T1D was precise and clinically verified, which facilitated the inclusion of patients diagnosed after 30 years of age. Almost 1 in 3 patients in our T1D population was diagnosed after 30 years of age, which is in accordance with the distribution found in other studies 12,52 ; information on this group of patients is particularly scarce in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…The diagnosis of T1D was precise and clinically verified, which facilitated the inclusion of patients diagnosed after 30 years of age. Almost 1 in 3 patients in our T1D population was diagnosed after 30 years of age, which is in accordance with the distribution found in other studies 12,52 ; information on this group of patients is particularly scarce in the literature.…”
Section: Discussionsupporting
confidence: 77%
“…In the same study these authors identified two cohorts (children born in 1985 and 1995) with sharp increases of incidence. Examinations in Italy (8,9) showed a general drift in the period and birth cohort, and in a Finish study (21), a period effect was shown, but a birth cohort effect was not found to be statistically significant. Rewers et al (10) reported that the incidence of type 1 diabetes in a Polish county showed a significant period effect, but no similar period effect was found for a U.S. county.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…The annual T2DM incidence increases from < 0.1% below the age of 30 to 1% around the age of 70 years (e.g. [8][9][10]). Currently, in Europe and the USA the prevalence of diabetes peaks around an age of 70 years, at 10 to 20% [11,12].…”
Section: A Brief Update On T2dmmentioning
confidence: 99%